2002
DOI: 10.1016/s0014-5793(02)02649-2
|View full text |Cite
|
Sign up to set email alerts
|

Action pattern and subsite mapping of Bacillus licheniformis α‐amylase (BLA) with modified maltooligosaccharide substrates

Abstract: This study represents the first characterisation of the substrate-binding site of Bacillus licheniformis K K-amylase (BLA). It describes the first subsite map, namely, number of subsites, apparent subsite energies and the dual product specificity of BLA. The product pattern and cleavage frequencies were determined by high-performance liquid chromatography, utilising a homologous series of chromophore-substituted maltooligosaccharides of degree of polymerisation 4^10 as model substrates. The binding region of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 28 publications
2
52
0
4
Order By: Relevance
“…Based on the cleavage pattern of a ρNP-maltoheptaoside, recently published for BLA (Kandra et al, 2002, and Fig. 2), and reports in the literature related to the maltosidase activities of various α-amylases, the production of G 2 ρNP and G 3 ρNP in addition to ρNP release is suggested.…”
Section: Methodsmentioning
confidence: 95%
“…Based on the cleavage pattern of a ρNP-maltoheptaoside, recently published for BLA (Kandra et al, 2002, and Fig. 2), and reports in the literature related to the maltosidase activities of various α-amylases, the production of G 2 ρNP and G 3 ρNP in addition to ρNP release is suggested.…”
Section: Methodsmentioning
confidence: 95%
“…The low -limit dextrin content of the samples having low branch point density is in accordance with the specific action of -amylase on linear -1,4 chains. A previous study (Kandra, Gyémánt, Remenyik, Hovánszki and Lipták, 2002) demonstrated that the maximum frequency of α-amylase attack site is shifted towards the reducing end with longer chain length. Therefore, our data do not exclude that the distance between each branch points in the products were shorter or equal to four glucose units (Fig.…”
Section: α-Limit Dextrin Structure and β-Amylolysis Limitmentioning
confidence: 91%
“…Action patterns on 4-nitrophenyl a-D D-maltopentaoside, -hexaoside, and -heptaoside of the best characterized plant a-amylases [10], the barley isozymes AMY1, AMY2 and AMY1 mutants, emphasized the relationship between subsite site structures and productive substrate binding modes [11][12][13][14]. Longer MOS, however, are needed for accurate analysis of affinities in bacterial and plant aamylases with P 9 subsites long binding sites [3,[7][8][9]15,16]. Here, subsite mapping of AMY1 (including mutants at outer subsites) and AMY2 using a unique DP 3-12 2-chloro-4-nitrophenyl (CNP) MOS series [4,16], highlights the dynamic substrate affinity landscape and provides a rationale for reorganisation of binding energies through protein engineering.…”
Section: Introductionmentioning
confidence: 99%